2020
DOI: 10.3989/scimar.05046.30a
|View full text |Cite
|
Sign up to set email alerts
|

Importance of recreational shore angling in the archipelago of Madeira, Portugal (northeast Atlantic)

Abstract: In 2017, a total of 4825 licences were issued for shore angling in Madeira. Surveys were conducted on 734 anglers, some in the government fisheries office during the licence request and others during the fishing activity. Shore angling is practised throughout the year, mostly at weekends and during day time, and with an increase in summer. More than 60% of the anglers are unemployed, have low incomes, and spend on average €254 per person per year on this activity, adding up to a total of €1.16 million per year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…The absence or low number of women fishers is a recurrent characteristic of recreational boat fishing, as observed in other studies from different parts of the world (Lloret et al 2008, Diogo and Pereira 2013, Ryan et al 2013). This contrasts with the relatively high proportion of women fishers in Madeira (in comparison with other regions), around 10%, but they are mostly restricted to other modalities, especially shore angling and limpet collection (Martínez-Escauriaza et al 2020a, Hermida andCosta 2020). The average age of recreational boat fishers was similar to that of shore angling fishers (42.9; Martínez-Escauriaza et al 2020a), but they were older than spearfishers, an activity which tends to attract younger people with an average age of 32.8 (Martínez-Escauriaza et al 2020b).…”
Section: Recreational Boat Fishers' Characteristics and Opinionsmentioning
confidence: 58%
See 2 more Smart Citations
“…The absence or low number of women fishers is a recurrent characteristic of recreational boat fishing, as observed in other studies from different parts of the world (Lloret et al 2008, Diogo and Pereira 2013, Ryan et al 2013). This contrasts with the relatively high proportion of women fishers in Madeira (in comparison with other regions), around 10%, but they are mostly restricted to other modalities, especially shore angling and limpet collection (Martínez-Escauriaza et al 2020a, Hermida andCosta 2020). The average age of recreational boat fishers was similar to that of shore angling fishers (42.9; Martínez-Escauriaza et al 2020a), but they were older than spearfishers, an activity which tends to attract younger people with an average age of 32.8 (Martínez-Escauriaza et al 2020b).…”
Section: Recreational Boat Fishers' Characteristics and Opinionsmentioning
confidence: 58%
“…Among all the recreational fishing modalities, a higher percentage of boat fishers (8.5%) admitted to selling their catches, followed by spearfishers (6.9%; Martínez-Escauriaza et al 2020b) and shore anglers (3.5%; Martínez-Escauriaza et al 2020a). This percentage is surely underestimated for all the modalities, because many fishers who sell their catch illegally are reluctant to admit it in a questionnaire.…”
Section: Recreational Boat Fishers' Characteristics and Opinionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies also reported strong recreational fishing pressures, reaching annual catches of almost 12,000 t in the Canary Islands (Gordoa, 2019) and 1,500 t in Madeira (Martínez-Escauriaza et al, 2020a,b). In Madeira, many recreational fishermen have reported a decrease in catches, and attribute this to both (i) the generalized degradation of coastal systems, and (ii) the fishing of individuals below the minimum landing size (Hermida and Delgado, 2016;Martínez-Escauriaza et al, 2020a). Fish biomass is more than three times higher in Selvagens than Madeira (Friedlander et al, 2017).…”
Section: Overfishingmentioning
confidence: 99%
“…Subsequently, sea urchin populations flourish as more individuals are recruited, and they reach larger sizes. The high recreative fishing activity on the coast of Madeira has been studied (Martínez-Escauriaza et al 2020a, 2020b in addition to the effect of the predation of D. africanum on macroalgae (Alves et al 2003). Other grazers, such as the sea urchins Arbacia lixula and herbivorous fishes (Sparisoma cretense and Sarpa salpa), also contribute to the consumption of Sargassaceae species (Verges et al 2009).…”
Section: Possible Causes and Impactsmentioning
confidence: 99%